1987
DOI: 10.1136/ard.46.4.307
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear leucocyte function and previous yersinia arthritis: enhanced chemokinetic migration and oxygen radical production correlate with the severity of the acute disease.

Abstract: SUMMARY Polymorphonuclear leucocyte (PMN) functions (migration in vitro, chemiluminescence, 02 production, binding of chemotactic peptide, and aggregation) were studied in HLA-B27 positive patients with previous yersinia arthritis (YA). PMNs of patients whose disease had been severe showed chemokinetic and chemiluminescence responses significantly higher than the PMNs of those with a mild disease. The results support the view that enhanced PMN function contributes to inflammatory symptoms in patients with YA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…4 We have also previously shown that PMN of the patients who have sequelae tend to show increased migration.5 These findings support the view that among patients with reactive arthritis there are subgroups with hyperreactive neutrophils, which may contribute to the development of severe inflammatory symptoms. Clinical studies also provide evidence of subgroups: according to the 10 year follow up study about 30% of patients with yersinia arthritis develop sacroiliitis, even ankylosing spondylitis.38 It is interesting that purified PMN of patients with ankylosing spondylitis show increased chemotactic responses to ZTS39 4 but not to FMLP,4' both under agarose and in the filter.…”
Section: Discussionsupporting
confidence: 61%
“…4 We have also previously shown that PMN of the patients who have sequelae tend to show increased migration.5 These findings support the view that among patients with reactive arthritis there are subgroups with hyperreactive neutrophils, which may contribute to the development of severe inflammatory symptoms. Clinical studies also provide evidence of subgroups: according to the 10 year follow up study about 30% of patients with yersinia arthritis develop sacroiliitis, even ankylosing spondylitis.38 It is interesting that purified PMN of patients with ankylosing spondylitis show increased chemotactic responses to ZTS39 4 but not to FMLP,4' both under agarose and in the filter.…”
Section: Discussionsupporting
confidence: 61%